Increased Stability of SARS-CoV-2 Omicron Variant over Ancestral Strain - Alex Wing Hong Chin; Alison Man Yuk Lai; Malik Peiris; Leo Lit Man Poon (Emerging Infectious Diseases, 2022)
As of April 2022, the Omicron BA.1 variant of concern of SARS-CoV-2 was spreading quickly around the world and outcompeting other circulating strains. We examined its stability on various surfaces and found that this Omicron variant is more stable than its ancestral strain on smooth and porous surfaces.